Matrisome Properties of Scaffolds Direct Fibroblasts in Idiopathic Pulmonary Fibrosis - Elowsson Rendin, Linda (Int J Mol Sci, 2019)
In idiopathic pulmonary fibrosis (IPF) structural properties of the extracellular matrix (ECM) are altered and influence cellular responses through cell-matrix interactions. Scaffolds (decellularized tissue) derived from subpleural healthy and IPF lungs were examined regarding biomechanical properties and ECM composition of proteins (the matrisome). Scaffolds were repopulated with healthy fibroblasts cultured under static stretch with heavy isotope amino acids (SILAC), to examine newly synthesized proteins over time. IPF scaffolds were characterized by increased tissue density, stiffness, ultimate force, and differential expressions of matrisome proteins compared to healthy scaffolds. Collagens, proteoglycans, and ECM glycoproteins were increased in IPF scaffolds, however while specific basement membrane (BM) proteins such as laminins and collagen IV were decreased, nidogen-2 was also increased. Findings were confirmed with histology, clearly showing a disorganized BM. Fibroblasts produced scaffold-specific proteins mimicking preexisting scaffold composition, where 11 out of 20 BM proteins were differentially expressed, along with increased periostin and proteoglycans production. We demonstrate how matrisome changes affect fibroblast activity using novel approaches to study temporal differences, where IPF scaffolds support a disorganized BM and upregulation of disease-associated proteins. These matrix-directed cellular responses emphasize the IPF matrisome and specifically the BM components as important factors for disease progression.